Spectrum of human tails: A report of six cases - Biswanath Mukhopadhyay; Ram M Shukla; Madhumita Mukhopadhyay; Kartik C Mandal; Pankaj Haldar; Abhijit Benare (Wolters Kluwer Medknow Publications, 2012)
Human tail is a curiosity, a cosmetic stigma and presents as an appendage in the lumbosacral region. Six patients of tail in the lumbosacral region are presented here to discuss the spectrum of presentation of human tails. The embryology, pathology and treatment of this entity are discussed along with a brief review of the literature.